Sport and Development in Emerging Nations - Knott, Brendon; Tinaz, Cem (2021)
For the first time, this book examines the strategies of leaders of emerging nations to use sport as a tool for reaching social, economic, cultural, political, technological or environmental goals and gaining international prestige. It assesses whether sport can really be an effective tool in international development.The book explores the unique challenges, issues and opportunities offered by sport for development in emerging nations. Bringing together case studies of sport and development in countries including Brazil, China, Czech Republic, Hungary, India, Indonesia, Mexico, Poland, Qatar, South Africa, South Korea and Turkey, the book looks at policies designed to achieve development through, by and for sport, and whether they have achieved their socio-economic objectives. It considers the way that emerging nations have used major international sports events as political and developmental projects, as well as the importance of sporting infrastructure, professional leagues, participation programmes and the influence of nationalism and ideology.With a truly global perspective, this book is important reading for any student, researcher or policy-maker with interest in sport management, sport development, development studies, international economics, globalisation or political science.